Planar‐Chiral Secondary Ferrocenylphosphanes. Issue 2 (6th October 2016) - Pandey, Souvik; Sárosi, Menyhárt B.; Lönnecke, Peter; Hey‐Hawkins, Evamarie
Abstract : An efficient way to obtain pure diastereomeric mixtures of C‐chiral, P‐chiral, planar‐chiral ferrocenylphosphanes is demonstrated by ortho ‐lithiation of enantiomerically pure ( S C )‐ N, N ‐dimethyl‐1‐ferrocenylethylamine (Ugi's amine) and reaction with RPX2 [X = Cl, Br; R = t Bu, 2, 4, 6‐Me3 C6 H2 (Mes)]. Four secondary ferrocenylphosphanes [Fe(C5 H5 )(1‐PHR‐2‐CHR′NMe2 ‐C5 H3 )] [R′ = H, R = t Bu (1 ); R′ = H, R = Mes (2 ); R′ = CH3, R = t Bu (3 ); R′ = CH3, R = Mes (4 )] were synthesised and characterised. Pure diastereomeric mixtures of 1 and 2, a mixture of the pure major diastereomers of 4, as well as diastereomerically pure 3 were obtained by column chromatography under a nitrogen atmosphere. The formation of amine–borane or phosphane–borane adducts was studied by 11 B and 31 P NMR spectroscopy. A theoretical study was performed to understand the tendency of 1 –4 toward borane adduct formation. Abstract : An efficient way to obtain diastereomerically pure chiral secondary ferrocenylphosphane derivatives derived from Ugi's amine is described. The formation of amine–borane or phosphane–borane adducts was studied by 11 B and 31 P NMR spectroscopy. A theoretical study was performed to understand the tendency toward borane adduct formation.